DEVELOPING A THAI READS ENCODER TO GAUGE EFL READING PROFICIENCY OF THAI UNDERGRADUATE STUDENTS - Thapanee Khemanuwong; Abdul Rashid Mohamed; Shaik Abdul Malik Mohamed Ismail (Siliwangi University, 2018)
Reading is not simply an understanding of graphic symbols, but it is also the interaction between a language and thoughts as it is a message coded in written form that needs to be understood. A very vital skill to master, reading has become an essential component of English as a Foreign Language (EFL) programme that inevitably needs an evaluation part. The component, however, provides no specific information about possessed performance of each student. Presently, there is an existing READS (Reading Evaluation and Decoding System) used as a diagnostic tool in assessing new intake of English reading proficiency at Universiti Sains Malaysia beginning in the academic year of 2014-2015. The existing READS, however, is specifically used on the basis of Malaysian school curricula and apparently has Malaysian culture embedded in its encoder. As a result, the encoder presents a significant amount of contextual biases. This study aims at developing a Thai localised version of READS encoder to serve as an indication of the specific skills each student possesses. A model Thai READS was developed and piloted to more than six hundred Thai undergraduate students in evaluating the students’ performance. The study revealed that the Thai variation of READS is effective in evaluating the students’ performance and decoding their reading skills.